2014
DOI: 10.1007/s00441-013-1788-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical analysis of misplaced rhodopsin-positive cells in the developing rodent retina

Abstract: During the first postnatal weeks of the developing rodent retina, rhodopsin can be detected in a number of neuron-like cells in the inner retina. In the present study, we aim to characterize the morphology, number and staining characteristics of this peculiar population. Misplaced rhodopsin-positive cells (MRCs) were analyzed on retinas of four rodent species, labeled with various rhodopsin-specific antibodies. To investigate their possible relation with non-photoreceptor cells, sections were double-stained ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…A small sub-population of cones displaced to the inner retina has been previously reported in the rat and human retina (Semo et al, 2007), consistent with the findings reported here in mice. Similarly, a small population of displaced rod photoreceptors has been observed in the rat retina, but these cells appear to be eliminated by adulthood (Gunhan et al, 2003; Szabo€ ´ et al, 2014). In contrast, our data indicate that at least some DCs remain in the adult mouse retina and the continued presence of ipRGCs is required to restrict their numbers, as evidenced by the elevated number of DCs in adult Opn4 DTA/DTA retinas compared to controls.…”
Section: Discussionmentioning
confidence: 77%
“…A small sub-population of cones displaced to the inner retina has been previously reported in the rat and human retina (Semo et al, 2007), consistent with the findings reported here in mice. Similarly, a small population of displaced rod photoreceptors has been observed in the rat retina, but these cells appear to be eliminated by adulthood (Gunhan et al, 2003; Szabo€ ´ et al, 2014). In contrast, our data indicate that at least some DCs remain in the adult mouse retina and the continued presence of ipRGCs is required to restrict their numbers, as evidenced by the elevated number of DCs in adult Opn4 DTA/DTA retinas compared to controls.…”
Section: Discussionmentioning
confidence: 77%
“…The antibody against GFAP was raised using GFAP from pig spinal cord as immunogen, and shown by the supplier to reacts specifically with GFAP in immunoblotting assays. Its reactivity in the retina has also been established in the rat (Enzsoly et al, ; Lieth et al, ) and in other rodent species (Szabo, Szabo, Enzsoly, Szel, & Lukats, ). The staining pattern in M.sh was identical, mostly restricted to astrocytes and the end feet of Müller cells in control specimens, while showing a more or less prominent upregulation in Müller cells in hyperglycemic specimens.…”
Section: Methodsmentioning
confidence: 87%
“…Amino acids 651–672 at the C‐terminus of PKC‐α of human origin was used to produce the antibody applied in the study. The staining of rod bipolar cells (and some amacrine cells) in the rodent retina is well documented (Enzsoly et al, ; Greferath, Grunert, & Wassle, ; Szabo, Szabo, Enzsoly, Szel, & Lukats, ) and staining in M.sh . gave practically identical results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Rhodopsin, a photopigment of the G-protein-coupled protein superfamily, is present only in rod PRs, thus considered a marker for rod PRs. 33 To identify cone PRs, we use cone arrestin. Arrestins are a superfamily of regulatory proteins involved in G-protein-coupled receptor (GPCR) desensitization, internalization, and GPCR-mediated activation of mitogen-activated protein kinase pathways.…”
Section: Resultsmentioning
confidence: 99%